Case report: Pathological differences in pulmonary arterial hypertension in long-term responders to calcium channel blockers - Tamura, Yuichi; Lkhagvadorj, Sayamaa; Tamura, Yudai; Furukawa, Asuka; Aida, Shinsuke; Ebinuma, Hirotoshi; Shiomi, Takayuki (Frontiers in Cardiovascular Medicine, 2023)
Background This study investigates the pulmonary arterial histopathology in patients with idiopathic pulmonary arterial hypertension (IPAH) and acute vasoreactive phenotype, who demonstrated long-term survival (>30 years) and incidental death from causes other than PAH progression. The pathological changes observed in these patients were compared with those in patients with bone morphogenetic protein receptor type 2 (BMPR2) mutation. Case Presentation We present two cases of patients with pulmonary arterial hypertension (PAH) who died incidentally from causes unrelated to PAH progression. We report compares pulmonary arterial histopathology in long-term survivors of CCB-responsive PAH patient and a hereditary PAH patient with a BMPR2 mutation. Lung specimens were analyzed using the Heath and Edwards (HE) classification and percentage muscular wall thickness (%MWT) of pulmonary arterioles. A significant difference in the severity of grading (p = 0.0001) and distribution between grades 1-2, 4 (p = 0.001), and 5 (p = 0.014) was observed between both patients. These findings suggest differential vascular pathology between the two cases, with CCB responders displaying more mild illness lesions compared to BMPR2 mutant patients. Conclusion The study revealed that CCB responders exhibit more mild illness vascular lesions than BMPR2 mutant patients despite their long-term survival, suggesting a difference in vascular pathology between the two phenotypes.